(untitled) (Research, Society and Development, 2023)
Bisphosphonates are a class of drugs used in the treatment of diseases that cause bone resorption, including osteoporosis, Paget’s disease of the bone, as well as diseases linked to malignancy such as multiple myeloma. One of its mechanisms of action is the inhibition of osteoclast activity. Since 2003, studies have reported the association of avascular osteonecrosis of the maxillary bones with the use of bisphosphonates, being an example of an adverse reaction. Several signs and symptoms result in its clinical manifestations, due to complications in the therapy of bisphosphonates, and may be asymptomatic or, in some cases, present with pain and necrosis when there is exposure of the mandibular or maxillary bone. Thus, the objective of this study was to carry out a literature review about the relationship between osteonecrosis of the jaws and the use of bisphosphonates. In order to carry out this literature review, scientific articles researched in English and Portuguese with no limit of year of publication in the following databases were evaluated: PubMed, SciELO (Scientific Electronic Library Online, Scopus Elsevier, BVS (Virtual Health Library) and Academic Google. Using the descriptors: “Bisphosphonate, Osteonecrosis, Jaws, Dentistry”. It is concluded that osteonecrosis of the jaws is a disease that may be related to the use of bisphosphonates, and that there is still no standard treatment for this pathology, Ideally, before starting treatment with bisphosphonates, the patient should undergo a dental appointment to carry out possible invasive treatments and achieve good oral health.